Gravity waves above the Andes detected from GPS radio occultation temperature profiles: Jet mechanism? - de la Torre, A. (2006)
A significant wave activity (WA) in the upper troposphere and lower stratosphere, mainly during winter, was detected at midlatitudes in the southern hemisphere (30-40S) above the Andes Range, from an analysis of Global Positioning System Radio Occultation (GPS RO) temperature profiles retrieved by CHAMP (CHAllenging Mini-satellite Payload) and SAC-C (Satélite de Aplicaciones Científicas-C) Low Earth Orbit (LEO) satellites, between May 2001 and February 2006. The possible main gravity wave sources in this region are: i) orographic forcing, ii) geostrophic adjustment and iii) deep convection. The available vertical resolution of GPS RO soundings does not rule out any of these alternatives. Based on satellite imaginary, the WA enhancements cannot be attributed to deep convection events. Inertia-gravity waves (IGWs) could be generated after a geostrophic adjustment process, following a perturbation of the zonal jet situated above the Andes Mountains by mountain waves (MWs). The monthly WA intensity follows the zonal wind velocity strength according to its seasonal variability at jet altitudes. As the GPS-LEO lines of sight are roughly meridionally aligned and the morphology of the Andes at middle latitudes is predominantly north-south, it was possible to detect MWs as well as IGWs from GPS RO temperature profiles. This characteristic does not apply for other mountain range alignments. From the analysis of a numerical simulation at the time and location of a single RO event with very strong WA, two main modes of oscillation with horizontal wavelength around 40 and 200 km were identified. The first one is attributed to a MW and the second one to an IGW. Copyright 2006 by the American Geophysical Union.